Thinking about returning home from a protected haematology unit: confronting healthcare providers’ representations and patients’ experiences in a qualitative study - Letrecher, Sandrine; Chemrouk, Yasmine; Sani, Livia (Frontiers in Psychology, 2025)
BackgroundThe psychological impact of protective isolation in haematology has been widely studied during hospitalization, but little is known about what happens when patients return home.AimDrawing on two qualitative studies conducted in French hospitals—one with patients and one with healthcare providers—this article explores how both groups experience the transition out of protective isolation. The focus is on the psychological challenges of returning home, shifts in identity and family roles, and the emotional dynamics between patients and staff.MethodsThis article presents findings from two qualitative studies in clinical psychology. The first involved 10 non-directive interviews conducted with patients following their discharge from a Protected Haematology unit; the data was analyzed using grounded theory and narrative analysis. The second study comprised 12 semi-structured interviews with healthcare professionals, analyzed through interpretative phenomenological analysis (IPA).ResultsReturning home poses significant challenges for patients and their families. Sterile constraints often persist, and hospital discharge does not necessarily signify recovery. At home, patients must navigate ongoing difficulties, including strict hygiene protocols, dependence on others, frequent medical appointments, and profound identity shifts related to illness. Healthcare professionals face a double bind: they are expected to celebrate the patient’s discharge while recognizing that it does not mark the end of isolation. In end-of-life contexts, they may emotionally distance themselves from patients—a defense mechanism that protects them from the grief associated with high mortality rates in oncology and haematology.ConclusionThe findings underscore the importance of dedicated spaces for reflection and dialogue—at home, to support patients and their families, and within hospital settings, to enable healthcare professionals to process potentially traumatic experiences.